Using the Fed Challenge to provide experiential learning of monetary policy. (2016) - Crook, Michelle A.
This paper describes how an experiential learning opportunity known as the Fed Challenge, coaching teaching methods, and active learning activities can promote a practical application of monetary policy in the discipline of economics. Readers are encouraged to consider if these teaching methods and activities could be incorporated into their own courses or if such experiential learning opportunities could be sought at their respective colleges or universities.